Three case studies of nonparaneoplastic limbic encephalitis (NPLE) in young adult males: Onset, course, and recovery following rehabilitation services. Issue 1 (2nd January 2019) - Perna, Robert; Harik, Lindsey; Arenivas, Ana
ABSTRACT: Limbic encephalitis (LE) is a rare neurological disorder characterized by inflammation of the brain caused by autoimmunity or infection. LE has been a difficult to define and diagnose disorder due to the insidious and nonspecific (e.g., irritability, low mood, short-term memory complaints) presentation of early symptoms, as well as inconsistent findings on neuroimaging, lumbar puncture serum analysis, and electroencephalogram. Seizures, memory problems, and psychiatric disturbance are among the earliest and most prominent clinical features. This manuscript describes three adolescent males who developed LE and became psychotic, needed inpatient care, were trialed on various psychotropic medications, and exhibited lingering cognitive and psychiatric issues, though generally had very positive recoveries and return to community activities. There was no history of psychiatric disturbance, developmental disorder, or learning difficulties in any of these three young men. Two of the three cases exhibited a long, insidious symptom onset. None of the adolescents benefitted from antipsychotic medications and did not begin to experience improvement and eventual recovery until intravenous immunoglobulin (IVIG) was added to their treatment regimen. Neuropsychological consultation and team education was helpful in each of these cases. Neuropsychological findings for each individual are presented.